Predictors of administrative innovation: functions and organizational methods -Mexican and Colombian hospitals- - Moreno, Eréndira Fierro; Mata, José Luis Cantú; Bello, Joel Martínez; López M., Oscar Hernán (Review of Business Management, 2015)
Objective – To determine to what extent functions and organizational methods influence on administrative innovation. Design/methodology/approach – This research is quantitative approach, with a not experimental and transversal design. The hypothesis was supported by using a transactional study with a sample of Mexican and Colombian hospitals through the perception of their high and medium level managers. The hospital sampling was by convenience. Findings - Organizational functions and methods are associated and are predictors of administrative innovation. Practical implications – As long as the hospital encourages the development of training and knowledge methods, autonomy methods for employees are developed, and when performance appraisal takes place in hospital, new methods will be able to develop and organize the routines and the management procedures, allocation of responsibilities and power among employees could be developed, as well as to develop new structure concepts for workplace, organizational practices and external relationships.